(untitled) (Al-Farooq Journal of Sciences, 2026)
This research investigates household solid waste pollution in Msallata city, focusing on its spatial causes, environmental impacts, and proposed management solutions. The study reveals an intensifying ecological and economic crisis resulting from the absence of an integrated and sustainable urban waste management system. Field observations indicate that collection, transportation, and storage are conducted through traditional practices with limited infrastructure, lacking waste segregation or recycling mechanisms. Furthermore, the urban landscape is devoid of sanitary landfills or treatment facilities, aggravating the environmental vulnerability of the city. Empirical results show that per capita waste generation is approximately one kilogram per day, amounting to over 61,320,000 tons annually—volumes that remain unmanaged within the urban ecosystem. The findings highlight structural constraints such as inadequate financial resources, shortage of skilled labor, weak institutional monitoring, and limited material and human capacities, all of which hinder effective spatial governance of waste. The study recommends the formulation of a comprehensive municipal waste management strategy grounded in sustainability principles. It emphasizes capacity-building for local human resources, the activation of media channels to enhance environmental awareness, and the strengthening of institutional cooperation between the municipality, governmental agencies, and private stakeholders. Such measures are essential to achieve efficient and sustainable waste governance and mitigate the environmental risks threatening the urban geography of Msallata.